PP-022 Paediatric chemotherapy preparation: An a priori risk assessment. (14th February 2016) - Mortier, CP; Duceau, J; Boivin, PN; Lester, MA; Gicquel, V
Abstract : Background: Preparing chemotherapies is a highly critical activity. Chemotherapy overdosage in paediatric units are part of the National Agency for Medicines and Health Product Safety's 'never events'. Therefore, risk management of related processes is compulsory. Purpose: Given the complexity of current local processes, including multiple re-transcriptions, no e-prescribing and ambiguous prescriptions, an a priori risk assessment was conducted. Considering the results, corrective actions were elaborated and their impact on overall risk was evaluated. Material and methods: The failure modes and effects analysis (FMEA) method was used to quantify the risk linked to the different phases of the process, including order reception, pharmaceutical validation, software re-transcription then preparation and delivery of the bags to the care unit. Each risk was rated, from 1 to 5, regarding the probability of occurrence (P), degree of severity (S) and detection capability (D). The criticality (C) of each step was determined by multiplying the scores: C = P×S×D. Results: Global risk score, linked to 29 critical steps, was 734. Preparation phases generated 27% of overall criticality. 63% was due to 'pre-preparation' steps: order reception, pharmaceutical validation and software re-transcription. The remaining 10% was due to raw material storage conditions and delivery modalities to the care unit. Given these results, short term improvements concerning prescription modalities such as mention of the protocol name, type and volume of the vehicle on the order, could lead to a risk reduction of 234 points. Identity monitoring enhancement could also lower the risk by 50 points. In the medium term, e-prescribing will lower the overall risk by 60% and the number of critical steps by 30%. Conclusion: This process assessment allowed us to determine which step can be easily optimised in order to improve safety and quality of care associated with paediatric chemotherapies, pending e-prescription introduction. References and/or Acknowledgements: http://ansm.sante.fr/Dossiers/Securite-du-medicament-a-l-hopital/Les-evenements-qui-ne-devraient-jamais-arriver-Never-Events/(offset)/0 No conflict of interest.